2021
DOI: 10.3390/ijms222312765
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated MicroRNAs as Biomarkers or Therapeutic Targets in Cisplatin-Induced Nephrotoxicity: A Systematic Review

Abstract: The purpose of this systematic review was to map out and summarize scientific evidence on dysregulated microRNAs (miRNAs) that can be possible biomarkers or therapeutic targets for cisplatin nephrotoxicity and have already been tested in humans, animals, or cells. In addition, an in silico analysis of the two miRNAs found to be dysregulated in the majority of studies was performed. A literature search was performed using eight databases for studies published up to 4 July 2021. Two independent reviewers selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 79 publications
0
9
0
6
Order By: Relevance
“…The drug cisplatin is frequently used in chemotherapy to damage the DNA of rapidly dividing cancer cells. Our findings reveal that increasing doses of cisplatin lead to increases in NAD­(P)­H levels in A549 cells (Figure ). One potential explanation for this observation is that DNA damage initiated by cisplatin stimulates the poly­(ADP-ribose) polymerase (PARP) pathway, which utilizes NAD + to synthesize poly­(ADP-ribose) (PAR) chains on damaged DNA.…”
Section: Results and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The drug cisplatin is frequently used in chemotherapy to damage the DNA of rapidly dividing cancer cells. Our findings reveal that increasing doses of cisplatin lead to increases in NAD­(P)­H levels in A549 cells (Figure ). One potential explanation for this observation is that DNA damage initiated by cisplatin stimulates the poly­(ADP-ribose) polymerase (PARP) pathway, which utilizes NAD + to synthesize poly­(ADP-ribose) (PAR) chains on damaged DNA.…”
Section: Results and Discussionmentioning
confidence: 71%
“…One potential explanation for this observation is that DNA damage initiated by cisplatin stimulates the poly­(ADP-ribose) polymerase (PARP) pathway, which utilizes NAD + to synthesize poly­(ADP-ribose) (PAR) chains on damaged DNA. PARylation can facilitate the mobilization of DNA repair factors to the damaged site and aid in the repair process. However, excessive PARylation can deplete NAD + , which can negatively affect cellular metabolism and energy production. Cells can replenish NAD + via the salvage pathway, where nicotinamide is converted to NAD + by the enzyme nicotinamide phosphoribosyltransferase (NAMPT).…”
Section: Results and Discussionmentioning
confidence: 99%
“…[ 25 ] Discovering effective biomarkers and studying their intrinsic molecular regulation pathways leading to kidney inflammation is one of the most promising methods to determine the target of early intervention with cisplatin‐induced AKI. [ 26–28 ] In this study, we found that in the injured HK‐2 cell model and AKI mouse models induced by cisplatin, miR‐486‐5p was upregulated, whereas HAT1 was downregulated. miR‐486‐5p regulates cisplatin‐induced nephrotoxicity probably through adjusting HAT1 expression in mice.…”
Section: Discussionmentioning
confidence: 75%
“…MiRNAs are a class of non-coding RNAs, approximately 20 bp in length, and essential regulators of gene expression ( Krol et al, 2010 ; Saliminejad et al, 2019 ). Besides being involved in a variety of cellular processes, whether physiological or pathological ( Small and Olson, 2011 ; Li et al, 2013 ; Zhang et al, 2017 ), circulating miRNAs are considered advantageous alternative biomarkers also because of their specific expression pattern in different tissues or pathological states ( Fan et al, 2016 ; Torso et al, 2021 ), relatively simple laboratory analysis methods, and stability in a variety of body fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first evidence of the role of miRNAs in kidney functions ( Kato et al, 2007 ; Ho et al, 2008 ), evidence associating miRNAs with AKI has become stronger. Some miRNA specimens were previously associated with apoptosis, necrosis, fibrosis, and inflammatory processes ( Fan et al, 2016 ; Torso et al, 2021 ), all essential stress responses in the pathogenesis of cisplatin nephrotoxicity ( Tang et al, 2023 ). However, their use as biomarkers in human cohorts has been poorly investigated ( Torso et al, 2021 ; Mahtal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%